A Framework for Assessing Mortality and Morbidity After Large-Scale Disasters - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
In the wake of a large-scale disaster, from the initial devastation through the long tail of recovery, protecting the health and well-being of the affected individuals and communities is paramount. Accurate and timely information about mortality and significant morbidity related to the disaster are the cornerstone of the efforts of the disaster management enterprise to save lives and prevent further health impacts. Conversely, failure to accurately capture mortality and significant morbidity data undercuts the nation's capacity to protect its population. Information about disaster-related mortality and significant morbidity adds value at all phases of the disaster management cycle. As a disaster unfolds, the data are crucial in guiding response and recovery priorities, ensuring a common operating picture and real-time situational awareness across stakeholders, and protecting vulnerable populations and settings at heightened risk. A Framework for Assessing Mortality and Morbidity After Large-Scale Disasters reviews and describes the current state of the field of disaster-related mortality and significant morbidity assessment. This report examines practices and methods for data collection, recording, sharing, and use across state, local, tribal, and territorial stakeholders; evaluates best practices; and identifies areas for future resource investment.
Keywords: Health and Medicine

Crisis Standards of Care: A Systems Framework for Catastrophic Disaster Response: Volume 1: Introduction and CSC Framework - Institute of Medicine (The National Academies Press, 2012)
Catastrophic disasters occurring in 2011 in the United States and worldwide—from the tornado in Joplin, Missouri, to the earthquake and tsunami in Japan, to the earthquake in New Zealand—have demonstrated that even prepared communities can be overwhelmed. In 2009, at the height of the influenza A (H1N1) pandemic, the Assistant Secretary for Preparedness and Response at the Department of Health and Human Services, along with the Department of Veterans Affairs and the National Highway Traffic Safety Administration, asked the Institute of Medicine (IOM) to convene a committee of experts to develop national guidance for use by state and local public health officials and health-sector agencies and institutions in establishing and implementing standards of care that should apply in disaster situations-both naturally occurring and man-made-under conditions of scarce resources. Building on the work of phase one (which is described in IOM's 2009 letter report, Guidance for Establishing Crisis Standards of Care for Use in Disaster Situations), the committee developed detailed templates enumerating the functions and tasks of the key stakeholder groups involved in crisis standards of care (CSC) planning, implementation, and public engagement-state and local governments, emergency medical services (EMS), hospitals and acute care facilities, and out-of-hospital and alternate care systems. Crisis Standards of Care provides a framework for a systems approach to the development and implementation of CSC plans, and addresses the legal issues and the ethical, palliative care, and mental health issues that agencies and organizations at each level of a disaster response should address. Please note: this report is not intended to be a detailed guide to emergency preparedness or disaster response. What is described in this report is an extrapolation of existing incident management practices and principles. Crisis Standards of Care is a seven-volume set: Volume 1 provides an overview; Volume 2 pertains to state and local governments; Volume 3 pertains to emergency medical services; Volume 4 pertains to hospitals and acute care facilities; Volume 5 pertains to out-of-hospital care and alternate care systems; Volume 6 contains a public engagement toolkit; and Volume 7 contains appendixes with additional resources.
Keywords: Health and Medicine; Conflict and Security Issues

Incorporating the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change—Guidebook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Extreme weather events and a changing climate increasingly boost costs to transportation agencies and to the traveling public. While Departments of Transportation (DOTs) are taking into account changing climate and extreme weather when making infrastructure decisions, they typically are not using a formal set of tools or cost-benefit analyses (CBAs) to address climate resilience because they may be too time-consuming and expensive to conduct routinely.The TRB National Cooperative Highway Research Program's NCHRP Research Report 938: Incorporating the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change—Guidebook was developed to try to fill the gaps identified by DOTs. It is intended to provide a consolidated resource for transportation practitioners to be able to more readily consider CBAs as a tool in their investment-decision making processes when considering different climate and extreme weather adaptation alternatives.This report has additional resources, including a web-only document NCHRP Web-Only Document 271: Guidelines to Incorporate the Costs andBenefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change, a Power Point presentation that describes the research and the results, a spreadsheet tool that provides an approximate test to see if it would be cost-effective to upgrade assets to the future conditions posed by climate change, and a spreadsheet tool that uses existing conditions without climate change only to calculate the new return period for future conditions with climate change.
Keywords: Transportation and Infrastructure

Building Community Disaster Resilience Through Private-Public Collaboration - National Research Council (The National Academies Press, 2011)
Natural disasters—including hurricanes, earthquakes, volcanic eruptions, and floods—caused more than 220,000 deaths worldwide in the first half of 2010 and wreaked havoc on homes, buildings, and the environment. To withstand and recover from natural and human-caused disasters, it is essential that citizens and communities work together to anticipate threats, limit their effects, and rapidly restore functionality after a crisis. Increasing evidence indicates that collaboration between the private and public sectors could improve the ability of a community to prepare for, respond to, and recover from disasters. Several previous National Research Council reports have identified specific examples of the private and public sectors working cooperatively to reduce the effects of a disaster by implementing building codes, retrofitting buildings, improving community education, or issuing extreme-weather warnings. State and federal governments have acknowledged the importance of collaboration between private and public organizations to develop planning for disaster preparedness and response. Despite growing ad hoc experience across the country, there is currently no comprehensive framework to guide private-public collaboration focused on disaster preparedness, response, and recovery. Building Community Disaster Resilience through Private-Public Collaboration assesses the current state of private-public sector collaboration dedicated to strengthening community resilience, identifies gaps in knowledge and practice, and recommends research that could be targeted for investment. Specifically, the book finds that local-level private-public collaboration is essential to the development of community resilience. Sustainable and effective resilience-focused private-public collaboration is dependent on several basic principles that increase communication among all sectors of the community, incorporate flexibility into collaborative networks, and encourage regular reassessment of collaborative missions, goals, and practices.
Keywords: Earth Sciences; Policy for Science and Technology; Conflict and Security Issues

Enabling Rapid and Sustainable Public Health Research During Disasters: Summary of a Joint Workshop by the Institute of Medicine and the U.S. Department of Health and Human Services - Institute of Medicine (The National Academies Press, 2015)
Over the past decade, preparedness and response capacities of government agencies, hospitals and clinics, public health agencies, and academic researchers in the United States and abroad have been challenged by a succession of public health emergencies, ranging from radiological threats to pandemics to earthquakes. Through After Action Reports, each of these emergencies has yielded important information and lessons learned that can inform future disaster response and recovery efforts. However, important information that needs to be collected during and immediately following these emergencies is often missed because of barriers and obstacles to gathering such data, such as varying institutional review board restrictions in different states, no sustainable funding network for this type of work, uncertainty on who should be involved in research response, and a lack of knowledge around how best to integrate research into response and recovery frameworks. Taking action to enable medical and public health research during disasters was the focus of a workshop held on June 12 and 13, 2014, coordinated and supported jointly by the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events, National Institute of Environmental Health Sciences, the National Library of Medicine, the U.S. Department of Health and Human Services' Office of the Assistant Secretary for Preparedness and Response, and the Centers for Disease Control and Prevention. Invited speakers and participants from federal, state, and local government, academia, and community and worker organizations came together to discuss how to integrate research into existing response structures; identify critical research needs and priorities; identify obstacles and barriers to research; discuss structures and strategies needed for deployment of a research study; share ideas, innovations, and technologies to support research; and explore data collection tools and data-sharing mechanisms for both rapid and longitudinal research. Enabling Rapid and Sustainable Public Health Research During Disasters summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Guidelines to Incorporate the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Cost-benefit analysis (CBA) is useful for climate change response and adaptation, and if used properly, it has great potential for long-range planning. CBA should help agencies navigate the spectrum of decisions from mitigation and greenhouse gas reduction to adaptation: where does investing public funds generate the most public good?The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 271: Guidelines to Incorporate the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change is published as a companion document to NCHRP Research Report 938. It includes two frameworks that were developed for the project to allow practitioners to conduct CBAs to a level of detail they deem appropriate; a sketch-level analysis can serve as a screening tool to evaluate if adaptation is even appropriate, while a more detailed climate resilience analysis can help to answer the question, “How much can I spend on an adaptation project and have it remain cost-effective?”
Keywords: Transportation and Infrastructure

Grand Challenges in Earthquake Engineering Research: A Community Workshop Report - National Research Council (The National Academies Press, 2011)
As geological threats become more imminent, society must make a major commitment to increase the resilience of its communities, infrastructure, and citizens. Recent earthquakes in Japan, New Zealand, Haiti, and Chile provide stark reminders of the devastating impact major earthquakes have on the lives and economic stability of millions of people worldwide. The events in Haiti continue to show that poor planning and governance lead to long-term chaos, while nations like Chile demonstrate steady recovery due to modern earthquake planning and proper construction and mitigation activities. At the request of the National Science Foundation, the National Research Council hosted a two-day workshop to give members of the community an opportunity to identify "Grand Challenges" for earthquake engineering research that are needed to achieve an earthquake resilient society, as well as to describe networks of earthquake engineering experimental capabilities and cyberinfrastructure tools that could continue to address ongoing areas of concern. Grand Challenges in Earthquake Engineering Research: A Community Workshop Report explores the priorities and problems regions face in reducing consequent damage and spurring technological preparedness advances. Over the course of the Grand Challenges in Earthquake Engineering Research workshop, 13 grand challenge problems emerged and were summarized in terms of five overarching themes including: community resilience framework, decision making, simulation, mitigation, and design tools. Participants suggested 14 experimental facilities and cyberinfrastructure tools that would be needed to carry out testing, observations, and simulations, and to analyze the results. The report also reviews progressive steps that have been made in research and development, and considers what factors will accelerate transformative solutions.
Keywords: Earth Sciences; Engineering and Technology

Successful Response Starts with a Map: Improving Geospatial Support for Disaster Management - National Research Council (The National Academies Press, 2007)
In the past few years the United States has experienced a series of disasters, such as Hurricane Katrina in 2005, which have severely taxed and in many cases overwhelmed responding agencies. In all aspects of emergency management, geospatial data and tools have the potential to help save lives, limit damage, and reduce the costs of dealing with emergencies. Great strides have been made in the past four decades in the development of geospatial data and tools that describe locations of objects on the Earth's surface and make it possible for anyone with access to the Internet to witness the magnitude of a disaster. However, the effectiveness of any technology is as much about the human systems in which it is embedded as about the technology itself. Successful Response Starts with a Map assesses the status of the use of geospatial data, tools, and infrastructure in disaster management, and recommends ways to increase and improve their use. This book explores emergency planning and response; how geospatial data and tools are currently being used in this field; the current policies that govern their use; various issues related to data accessibility and security; training; and funding. Successful Response Starts with a Map recommends significant investments be made in training of personnel, coordination among agencies, sharing of data and tools, planning and preparedness, and the tools themselves.
Keywords: Earth Sciences

Tsunami Warning and Preparedness: An Assessment of the U.S. Tsunami Program and the Nation's Preparedness Efforts - National Research Council (The National Academies Press, 2011)
Many coastal areas of the United States are at risk for tsunamis. After the catastrophic 2004 tsunami in the Indian Ocean, legislation was passed to expand U.S. tsunami warning capabilities. Since then, the nation has made progress in several related areas on both the federal and state levels. At the federal level, NOAA has improved the ability to detect and forecast tsunamis by expanding the sensor network. Other federal and state activities to increase tsunami safety include: improvements to tsunami hazard and evacuation maps for many coastal communities; vulnerability assessments of some coastal populations in several states; and new efforts to increase public awareness of the hazard and how to respond. Tsunami Warning and Preparedness explores the advances made in tsunami detection and preparedness, and identifies the challenges that still remain. The book describes areas of research and development that would improve tsunami education, preparation, and detection, especially with tsunamis that arrive less than an hour after the triggering event. It asserts that seamless coordination between the two Tsunami Warning Centers and clear communications to local officials and the public could create a timely and effective response to coastal communities facing a pending tsuanami. According to Tsunami Warning and Preparedness, minimizing future losses to the nation from tsunamis requires persistent progress across the broad spectrum of efforts including: risk assessment, public education, government coordination, detection and forecasting, and warning-center operations. The book also suggests designing effective interagency exercises, using professional emergency-management standards to prepare communities, and prioritizing funding based on tsunami risk.
Keywords: Earth Sciences; Conflict and Security Issues

American Hazardscapes: The Regionalization of Hazards and Disasters - Susan L. Cutter (The National Academies Press, 2001)
Barrier islands. Flood plains. Earthquake faults. Sometimes the environment poses threats to our well being, yet many of us continue to choose to live in risky or dangerous places. And on top of the “knowns” are the other, more hidden hazards related to environmental contamination that pose equally serious threats to our health and well being. But where are these places and what types of hazards are found there? American Hazardscapes examines the risks associated with living and owning property in diverse regions across the United States, offering dual perspectives: that of the geographer and that of the social science hazards researcher. The book summarizes what we already know about regional patterns of hazard events and losses during the previous three decades and goes further to shed light on the nature of the events themselves and their impact on society. Written for the relocating citizen and the policy maker alike, American Hazardscapes presents a regional ecology of disaster-prone or disaster-resistant states. It also offers thoughts on what local, state, and federal managers need to do to meet the challenge of reducing hazard losses in the next century.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine (The National Academies Press, 2015)
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a "return to normal." But for many American communities, pre-disaster conditions are far from optimal. Large segments of the U.S. population suffer from preventable health problems, experience inequitable access to services, and rely on overburdened health systems. A return to pre-event conditions in such cases may be short-sighted given the high costs - both economic and social - of poor health. Instead, it is important to understand that the disaster recovery process offers a series of unique and valuable opportunities to improve on the status quo. Capitalizing on these opportunities can advance the long-term health, resilience, and sustainability of communities - thereby better preparing them for future challenges. Healthy, Resilient, and Sustainable Communities After Disasters identifies and recommends recovery practices and novel programs most likely to impact overall community public health and contribute to resiliency for future incidents. This book makes the case that disaster recovery should be guided by a healthy community vision, where health considerations are integrated into all aspects of recovery planning before and after a disaster, and funding streams are leveraged in a coordinated manner and applied to health improvement priorities in order to meet human recovery needs and create healthy built and natural environments. The conceptual framework presented in Healthy, Resilient, and Sustainable Communities After Disasters lays the groundwork to achieve this goal and provides operational guidance for multiple sectors involved in community planning and disaster recovery. Healthy, Resilient, and Sustainable Communities After Disasters calls for actions at multiple levels to facilitate recovery strategies that optimize community health. With a shared healthy community vision, strategic planning that prioritizes health, and coordinated implementation, disaster recovery can result in a communities that are healthier, more livable places for current and future generations to grow and thrive - communities that are better prepared for future adversities.
Keywords: Health and Medicine; Conflict and Security Issues

Dam and Levee Safety and Community Resilience: A Vision for Future Practice - National Research Council (The National Academies Press, 2012)
Although advances in engineering can reduce the risk of dam and levee failure, some failures will still occur. Such events cause impacts on social and physical infrastructure that extend far beyond the flood zone. Broadening dam and levee safety programs to consider community- and regional-level priorities in decision making can help reduce the risk of, and increase community resilience to, potential dam and levee failures. Collaboration between dam and levee safety professionals at all levels, persons and property owners at direct risk, members of the wider economy, and the social and environmental networks in a community would allow all stakeholders to understand risks, shared needs, and opportunities, and make more informed decisions related to dam and levee infrastructure and community resilience. Dam and Levee Safety and Community Resilience: A Vision for Future Practice explains that fundamental shifts in safety culture will be necessary to integrate the concepts of resilience into dam and levee safety programs.
Keywords: Earth Sciences

Integrating Social and Behavioral Sciences Within the Weather Enterprise - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Our ability to observe and forecast severe weather events has improved markedly over the past few decades. Forecasts of snow and ice storms, hurricanes and storm surge, extreme heat, and other severe weather events are made with greater accuracy, geographic specificity, and lead time to allow people and communities to take appropriate protective measures. Yet hazardous weather continues to cause loss of life and result in other preventable social costs. There is growing recognition that a host of social and behavioral factors affect how we prepare for, observe, predict, respond to, and are impacted by weather hazards. For example, an individual's response to a severe weather event may depend on their understanding of the forecast, prior experience with severe weather, concerns about their other family members or property, their capacity to take the recommended protective actions, and numerous other factors. Indeed, it is these factors that can determine whether or not a potential hazard becomes an actual disaster. Thus, it is essential to bring to bear expertise in the social and behavioral sciences (SBS)—including disciplines such as anthropology, communication, demography, economics, geography, political science, psychology, and sociology—to understand how people's knowledge, experiences, perceptions, and attitudes shape their responses to weather risks and to understand how human cognitive and social dynamics affect the forecast process itself. Integrating Social and Behavioral Sciences Within the Weather Enterprise explores and provides guidance on the challenges of integrating social and behavioral sciences within the weather enterprise. It assesses current SBS activities, describes the potential value of improved integration of SBS and barriers that impede this integration, develops a research agenda, and identifies infrastructural and institutional arrangements for successfully pursuing SBS-weather research and the transfer of relevant findings to operational settings.
Keywords: Earth Sciences; Behavioral and Social Sciences

Evidence-Based Practice for Public Health Emergency Preparedness and Response - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
When communities face complex public health emergencies, state local, tribal, and territorial public health agencies must make difficult decisions regarding how to effectively respond. The public health emergency preparedness and response (PHEPR) system, with its multifaceted mission to prevent, protect against, quickly respond to, and recover from public health emergencies, is inherently complex and encompasses policies, organizations, and programs. Since the events of September 11, 2001, the United States has invested billions of dollars and immeasurable amounts of human capital to develop and enhance public health emergency preparedness and infrastructure to respond to a wide range of public health threats, including infectious diseases, natural disasters, and chemical, biological, radiological, and nuclear events. Despite the investments in research and the growing body of empirical literature on a range of preparedness and response capabilities and functions, there has been no national-level, comprehensive review and grading of evidence for public health emergency preparedness and response practices comparable to those utilized in medicine and other public health fields. Evidence-Based Practice for Public Health Emergency Preparedness and Response reviews the state of the evidence on PHEPR practices and the improvements necessary to move the field forward and to strengthen the PHEPR system. This publication evaluates PHEPR evidence to understand the balance of benefits and harms of PHEPR practices, with a focus on four main areas of PHEPR: engagement with and training of community-based partners to improve the outcomes of at-risk populations after public health emergencies; activation of a public health emergency operations center; communication of public health alerts and guidance to technical audiences during a public health emergency; and implementation of quarantine to reduce the spread of contagious illness.
Keywords: Health and Medicine

Reducing Coastal Risk on the East and Gulf Coasts - National Research Council (The National Academies Press, 2014)
Hurricane- and coastal-storm-related losses have increased substantially during the past century, largely due to increases in population and development in the most susceptible coastal areas. Climate change poses additional threats to coastal communities from sea level rise and possible increases in strength of the largest hurricanes. Several large cities in the United States have extensive assets at risk to coastal storms, along with countless smaller cities and developed areas. The devastation from Superstorm Sandy has heightened the nation's awareness of these vulnerabilities. What can we do to better prepare for and respond to the increasing risks of loss? Reducing Coastal Risk on the East and Gulf Coasts reviews the coastal risk-reduction strategies and levels of protection that have been used along the United States East and Gulf Coasts to reduce the impacts of coastal flooding associated with storm surges. This report evaluates their effectiveness in terms of economic return, protection of life safety, and minimization of environmental effects. According to this report, the vast majority of the funding for coastal risk-related issues is provided only after a disaster occurs. This report calls for the development of a national vision for coastal risk management that includes a long-term view, regional solutions, and recognition of the full array of economic, social, environmental, and life-safety benefits that come from risk reduction efforts. To support this vision, Reducing Coastal Risk states that a national coastal risk assessment is needed to identify those areas with the greatest risks that are high priorities for risk reduction efforts. The report discusses the implications of expanding the extent and levels of coastal storm surge protection in terms of operation and maintenance costs and the availability of resources. Reducing Coastal Risk recommends that benefit-cost analysis, constrained by acceptable risk criteria and other important environmental and social factors, be used as a framework for evaluating national investments in coastal risk reduction. The recommendations of this report will assist engineers, planners and policy makers at national, regional, state, and local levels to move from a nation that is primarily reactive to coastal disasters to one that invests wisely in coastal risk reduction and builds resilience among coastal communities.
Keywords: Earth Sciences

Facing the Unexpected: Disaster Preparedness and Response in the United States - Kathleen J. Tierney; Michael K. Lindell; Ronald W. Perry (The National Academies Press, 2001)
Facing the Unexpected presents the wealth of information derived from disasters around the world over the past 25 years. The authors explore how these findings can improve disaster programs, identify remaining research needs, and discuss disaster within the broader context of sustainable development. How do different people think about disaster? Are we more likely to panic or to respond with altruism? Why are 110 people killed in a Valujet crash considered disaster victims while the 50,000 killed annually in traffic accidents in the U.S. are not? At the crossroads of social, cultural, and economic factors, this book examines these and other compelling questions. The authors review the influences that shape the U.S. governmental system for disaster planning and response, the effectiveness of local emergency agencies, and the level of professionalism in the field. They also compare technological versus natural disaster and examine the impact of technology on disaster programs.
Keywords: Explore Science; Conflict and Security Issues

Tools and Methods for Estimating Populations at Risk from Natural Disasters and Complex Humanitarian Crises - National Research Council (The National Academies Press, 2007)
Worldwide, millions of people are displaced annually because of natural or industrial disasters or social upheaval. Reliable data on the numbers, characteristics, and locations of these populations can bolster humanitarian relief efforts and recovery programs. Using sound methods for estimating population numbers and characteristics is important for both industrialized and developing nations. Ensuring that the data are geographically referenced for projection onto maps is essential. However, good data alone are insufficient. Adequate staff training and strong organizational and political desire to maintain and use the information are also required. Tools and Methods for Estimating Populations at Risk from Natural Disasters and Complex Humanitarian Crises, reviews the main methods and tools for making estimates of subnational populations and makes several recommendations to improve the collection and the use of population data for emergency response and development.
Keywords: Behavioral and Social Sciences; Earth Sciences; Conflict and Security Issues

Improving Disaster Management: The Role of IT in Mitigation, Preparedness, Response, and Recovery - National Research Council (The National Academies Press, 2007)
Information technology (IT) has the potential to play a critical role in managing natural and human-made disasters. Damage to communications infrastructure, along with other communications problems exacerbated the difficulties in carrying out response and recovery efforts following Hurricane Katrina. To assist government planning in this area, the Congress, in the E-government Act of 2002, directed the Federal Emergency Management Agency (FEMA) to request the NRC to conduct a study on the application of IT to disaster management. This report characterizes disaster management providing a framework for considering the range and nature of information and communication needs; presents a vision of the potential for IT to improve disaster management; provides an analysis of structural, organizational, and other non-technical barriers to the acquisition, adoption, and effective use of IT in disaster; and offers an outline of a research program aimed at strengthening IT-enabled capabilities for disaster management.
Keywords: Computers and Information Technology; Earth Sciences; Conflict and Security Issues

Lessons Learned from the Fukushima Nuclear Accident for Improving Safety of U.S. Nuclear Plants - National Research Council (The National Academies Press, 2014)
The March 11, 2011, Great East Japan Earthquake and tsunami sparked a humanitarian disaster in northeastern Japan. They were responsible for more than 15,900 deaths and 2,600 missing persons as well as physical infrastructure damages exceeding $200 billion. The earthquake and tsunami also initiated a severe nuclear accident at the Fukushima Daiichi Nuclear Power Station. Three of the six reactors at the plant sustained severe core damage and released hydrogen and radioactive materials. Explosion of the released hydrogen damaged three reactor buildings and impeded onsite emergency response efforts. The accident prompted widespread evacuations of local populations, large economic losses, and the eventual shutdown of all nuclear power plants in Japan. Lessons Learned from the Fukushima Nuclear Accident for Improving Safety and Security of U.S. Nuclear Plants is a study of the Fukushima Daiichi accident. This report examines the causes of the crisis, the performance of safety systems at the plant, and the responses of its operators following the earthquake and tsunami. The report then considers the lessons that can be learned and their implications for U.S. safety and storage of spent nuclear fuel and high-level waste, commercial nuclear reactor safety and security regulations, and design improvements. Lessons Learned makes recommendations to improve plant systems, resources, and operator training to enable effective ad hoc responses to severe accidents. This report's recommendations to incorporate modern risk concepts into safety regulations and improve the nuclear safety culture will help the industry prepare for events that could challenge the design of plant structures and lead to a loss of critical safety functions. In providing a broad-scope, high-level examination of the accident, Lessons Learned is meant to complement earlier evaluations by industry and regulators. This in-depth review will be an essential resource for the nuclear power industry, policy makers, and anyone interested in the state of U.S. preparedness and response in the face of crisis situations.
Keywords: Conflict and Security Issues; Environment and Environmental Studies; Energy and Energy Conservation

Strengthening Post-Hurricane Supply Chain Resilience: Observations from Hurricanes Harvey, Irma, and Maria - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Resilient supply chains are crucial to maintaining the consistent delivery of goods and services to the American people. The modern economy has made supply chains more interconnected than ever, while also expanding both their range and fragility. In the third quarter of 2017, Hurricanes Harvey, Irma and Maria revealed some significant vulnerabilities in the national and regional supply chains of Texas, Florida, the U.S. Virgin Islands, and Puerto Rico. The broad impacts and quick succession of these three hurricanes also shed light on the effectiveness of the nation's disaster logistics efforts during response through recovery. Drawing on lessons learned during the 2017 hurricanes, this report explores future strategies to improve supply chain management in disaster situations. This report makes recommendations to strengthen the roles of continuity planning, partnerships between civic leaders with small businesses, and infrastructure investment to ensure that essential supply chains will remain operational in the next major disaster. Focusing on the supply chains food, fuel, water, pharmaceutical, and medical supplies, the recommendations of this report will assist the Federal Emergency Management Agency as well as state and local officials, private sector decision makers, civic leaders, and others who can help ensure that supply chains remain robust and resilient in the face of natural disasters.
Keywords: Conflict and Security Issues; Earth Sciences